Rasionalitas Agen Ekonomi: Eksperimen Ekonomi Menggunakan Beauty Contest Games - Siswanto, Bambang (Manajemen Bisnis Kompetensi, 2018)
Microeconomic theory assumes economic agents are rational when making decisions. In many ways numerical capabilities indicate a measure of the rationality of economic agents. Beauty contest games are one of the games commonly used in an experiment to show the failure of economic agents to make decisions based on numerical rationality. This article is written based on the results of economic experiments in the learning class (classroom experiments) using the BCG model with the aim of knowing the rationality of economic agents in making decisions. The results of the study show that economic agents do not fully act on numerical rationality so they cannot succeed in maximizing utility or achieving Nash equilibrium. Keywords : beauty contest game, guessing game, rationality, economic experiment, nash equilibrium